Utilization of Polypropylene (PP) Plastic Waste with Waste Oil Palm Empty Brunch for an Alternative Fuels - Putri Sakinah Harahap; Hutwan Syarifuddin; Nazarudin Nazarudin; Ulyarti Ulyarti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The need for plastic corresponds with the annual rise in population. Meanwhile, plastic waste that is improperly managed can negatively influence the environment. Therefore, a more promising alternative recycling process is needed to convert this waste into oil by cracking, and the process is possibly assisted by adding empty palm oil bunches. This study examines how modifications in the ratio of oil palm empty bunches to Polypropylene (PP) plastic waste influence the percent liquid produced by cracking and the heating value during the process. It is a completely randomized design (CRD) with variations in the ratio of plastic raw materials: oil palm empty fruit bunches 1:0, 1:1, 1:2, and 1:3 at a temperature of 450°C and 40 minutes duration. This resulted in liquid conversion from cracking of 80% at 1:1 of PP: TTKS 1:1. However, the addition of oil palm empty fruit bunches to polypropylene polymers does not affect the increase in the percent conversion outcomes. The results of the heat test analysis show the value of 6.681 MJ/kg and 1.512 MJ/kg. Keywords: Cracking, catalytic cracking, polypropylene plastic, biomass, alternative energy